Comparison of Propofol-Ketamine Combination with Propofol-Butorphanol Combination for Total Intravenous Anaesthesia on Short Surgical Procedures - Regmi, Nabin Kumar; Khatri, Santosh; Datta, Prashanta Kumar (Journal of Nepalgunj Medical College, 2016)
Objectives: The objective of this study was to compare propofol-ketamine combination with propofol-butorphanol combination for short surgical procedures in terms of hemodynamic and respiratory stability, postoperative sedation, postoperative nausea and vomiting and effect of abolishing pain on injection with propofol.Methods: This was a randomized double blinded study conducted in 60 patients belonging to ASA I &II, aged between 16 - 60 years. Patients were divided into two groups: Group-B: Propofol- Butorphanol combination (n=30) and Group-K: Propofol-Ketamine combination (n=30). The baseline values for the heart rate, mean arterial pressure and SPO recorded and every 5 minutes after induction of anesthesia.Results: In Butorphanol group MAP at 5, 10, 2 15, 20, 25 and 30 minutes after induction was significantly lesser but heart rate at 10, 15, 20, 25 and30 minutes after induction was significantly greater than in the Ketamine group with the p value of < 0.05. From 20-30 minutes post induction, SPO in Butorphanol 2 group was significantly less than in the Ketamine group with the p value of < 0.05. Pain after injection of propofol was significantly greater in Ketamine group with the p value of 0.008. There was no statistically significant sedation and post operative nausea and vomiting among the groups.Conclusion: Propofol-Ketamine combination provided better hemodynamic and respiratory stability than Propofol-Butorpanol combination however pain on injection with propofol was greater in Propofol-ketamine combination.JNGMC Vol. 12 No. 2 December 2014, Page: 34-39